ANALYSIS OF THE PROTECTIVE PROPERTIES OF FABRICS FOR SPECIAL CLOTHING OF OIL AND GAS EXTRACTION FIELD WORKERS AT HIGH TEMPERATURES - Chorieva, Мukhabbat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article studies the protective properties of fabrics intended for special clothing for workers in the oil and gas industry in Uzbekistan. Based on the conditions for the production of special clothing fabrics, the requirements for them are formed based on the norms specified in individual state standards.